(3cJGH cfGT UgGQHNJ aj GdWHs - (3UgGQHNJ HQeG SQLS GdeYQha HGHi jRjO GdeJWHHs; (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi de jRd bGd UgGQHNJ SGdJfi jGHi YjSi Rjfc Gddg HGdMceI Cf GTQM cd YhGjU JOHjQGJg hGLeY dc ef GdUdGLGJ GdeeJMfI eG GSJfHWg GdegQI GdMPGb ef GdGWHGA s
(3BNQgG (B:s
(3ai YdGL GdMejGJ GdJi Jchf eY GdehGVY GdCdeI agPG GeG NJefG Hg cJGHfG s
(3TQM GdeDda cJGH GdLO MhQLS GdfjSGHhQis
(3YdjgG ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdWHs